Proposing Core Practices for Social Studies Teacher Education: A Qualitative Content Analysis of Inquiry-Based Lessons. (May 2021) - Cuenca, Alexander
As states, school districts, and teachers continue to adopt the inquiry-based principles of the College, Career, and Civic (C3) Framework, social studies teacher education must engage in a concomitant instructional shift to focus its efforts on preparing inquiry-based educators. One possible approach is to organize social studies teacher education around core practices. In this study, I attempt to surface the core practices found in social studies classrooms through a qualitative content analysis of the lessons using the Inquiry Design Model (IDM), an instructional design process based on the elements of the C3 Framework. Seven core practices to organize social studies teacher education are proposed: (a) establishing social studies academic language, (b) helping students recognize the interdisciplinary nature of social studies phenomena, (c) using interpretive questions, (d) helping students organize inquiries, (e) connecting inquiries to students' lives, (f) structuring opportunities for discussion, and (g) extending inquiry into the civic lives of students.